X-ray excited optical luminescence of CaF2: A candidate for UV water treatment. (May 2015) - Chen, W; Ma, L; Schaeffer, R; Hoffmeyer, R; Sham, T; Belev, G; Kasap, S; Sammynaiken, R
Abstract: Secondary optical processes are becoming more and more important in health and environmental applications. Ultraviolet produced from secondary emission or scintillation can damage DNA by direct photoexcitation or by the creation of reactive oxygen species. X-ray Excited Optical Luminescence (XEOL) and Time Resolved XEOL (TRXEOL) results for the fast emitter, CaF2 :ZnO, that have been treated by heating in air and in vacuum, show that the scintillation from the Self Trapped Exciton (STE) emission of CaF2 at 282 nm is dominated by a slow process (>100 ns). A faster but weaker 10 ns component is also present. The ZnO and CaF2 show independent emission. The ZnO bandgap emission at 390 nm has dominant lifetimes of less than 1 ns.